The Development of Child Education Salman ITB 1984-2000 - Rofifah Ridha Nur’Adni; Yasmina Wikan Astri; Widiati Isana (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This study examines the history and development of Pembinaan Anak-Anak Salman, Institut Teknologi Bandung (PAS ITB), spanning from 1984 to 2000. This non-profit child education organization emerged from the initiative of ITB college students during the New Order era to coordinate children's activities around the Salman Mosque, ensuring they did not disrupt the congregation's prayers. Utilizing the historical research method—encompassing heuristics, source criticism (external and internal), interpretation, and historiography—this study analyzes the organizational structural dynamics through the lens of Edgar Schein’s Organizational Culture Theory and Talcott Parsons’ Structural Functionalism (AGIL framework). The findings reveal that between 1984 and 1994, PAS ITB underwent substantial institutional strengthening as an official unit of the Salman Mosque, driven by innovations in work programs, volunteer management, and infrastructure development. However, during the 1994–2000 period, the organization began encountering declines in student volunteer interest due to the relocation of a major partner university campus, stricter academic graduation policies, and the rapid growth of competing Islamic afternoon schools (TPA). Nevertheless, the synergy between the transmission of fundamental student dawah assumptions and robust structural governance successfully preserved PAS ITB's existence as an agent of social and religious change in the Ganesha Street area of Bandung.